2006
DOI: 10.1123/ijsnem.16.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Protein Added to a Sports Drink Improves Fluid Retention

Abstract: The purpose of this study was to compare fluid retention of carbohydrate plus protein, a carbohydrate-only, and water following 2.5% body weight (BW) loss. Thirteen subjects dehydrated to 2.5% of BW, then ingested a CHO (6%) plus protein drink (1.5%; CP), a 6% CHO drink, or water (WA) at a volume equal to BW loss during a 3-h recovery. Fluid retention was significantly greater for CP (88 +/- 4.7%) than CHO (75 +/- 14.6%), which was greater than WA (53 +/- 16.1%). Serum and urine osmolalities were greater for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
3
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 23 publications
2
80
3
2
Order By: Relevance
“…There The difference in findings between the studies of Seifert et al (2006) and James et al (2012) might be explained by the difference in rehydration drink volume ingested (100% vs. 150%) or the fact that the energy density of the rehydration drinks was either matched (James et al 2012) or unmatched (Seifert et al 2006). In the present study, the rehydration drinks were not matched for energy density and were ingested in a volume equivalent to 150% of subjects sweat losses, which is in line with current recommendations (Sawka et al 2007).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…There The difference in findings between the studies of Seifert et al (2006) and James et al (2012) might be explained by the difference in rehydration drink volume ingested (100% vs. 150%) or the fact that the energy density of the rehydration drinks was either matched (James et al 2012) or unmatched (Seifert et al 2006). In the present study, the rehydration drinks were not matched for energy density and were ingested in a volume equivalent to 150% of subjects sweat losses, which is in line with current recommendations (Sawka et al 2007).…”
Section: Discussionmentioning
confidence: 62%
“…Using G*Power 3.1.6 (Faul et al, 2009) and the data of Seifert et al (2006), an α of 0.05 and statistical power of 0.8, it was determined that nine subjects would be required to reject the null hypothesis.…”
Section: Participants and Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that when added in an energy matched fashion and when drinks are ingested in a volume equivalent to 150 % sweat loss, addition of milk protein (1) to a carbohydrate-electrolyte drink enhances rehydration, whilst the addition of whey protein isolate does not (2) . In contrast, Seifert et al (3) reported that when a volume of 100% sweat loss is ingested, the addition of whey protein to a carbohydrate-electrolyte drink in a non-energy matched fashion enhances rehydration. These studies have only examined the effect of protein addition to carbohydrate-electrolyte drinks and thus the purpose of the present study was to determine if whey protein effects rehydration in isolation with a rehydration volume sufficient to fully restore fluid balance after exercise (150 % sweat loss).…”
mentioning
confidence: 99%